2021
DOI: 10.3390/cells10030580
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a Neuroblastoma Model: Progress Made, Promise for the Future

Abstract: For nearly a decade, researchers in the field of pediatric oncology have been using zebrafish as a model for understanding the contributions of genetic alternations to the pathogenesis of neuroblastoma (NB), and exploring the molecular and cellular mechanisms that underlie neuroblastoma initiation and metastasis. In this review, we will enumerate and illustrate the key advantages of using the zebrafish model in NB research, which allows researchers to: monitor tumor development in real-time; robustly manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Tumors arising in Dbh-iCre;CAG-MYC closely mimic the histopathological and molecular features of human neuroblastoma, and respond to the FDA-approved immunotherapy and targeted therapy for neuroblastoma treatment. So far, all successful genetic neuroblastoma models have been based on the activation of MYC in either Th-or Dbh-positive cells [22][23][24][25][26][27][28] . Unexpectedly, we found that crossing of Dbh-Cre with CAG-MYC was unable to initiate tumorigenesis, suggesting that the Cre with improved coding sequences (iCre) has a better activity to drive c-MYC-mediated tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors arising in Dbh-iCre;CAG-MYC closely mimic the histopathological and molecular features of human neuroblastoma, and respond to the FDA-approved immunotherapy and targeted therapy for neuroblastoma treatment. So far, all successful genetic neuroblastoma models have been based on the activation of MYC in either Th-or Dbh-positive cells [22][23][24][25][26][27][28] . Unexpectedly, we found that crossing of Dbh-Cre with CAG-MYC was unable to initiate tumorigenesis, suggesting that the Cre with improved coding sequences (iCre) has a better activity to drive c-MYC-mediated tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent pan-neuroblastoma genomic analysis further confirmed previous studies showing that the most frequently altered genes were MYCN (19%, primarily amplification), TERT (17%; structural variations), SHANK2 (13%; structural variations), PTPRD (11%; structural variations and focal deletions), ALK (10%; somatic nucleotide variations and structural variations), and ATRX (8%, multiple mutation types) 11 . Genetically engineered mouse and zebrafish models of neuroblastoma have validated MYCN as a key oncogenic driver of neuroblastoma tumorigenesis, which can be promoted by other oncogenes such as ALK, LIN28B and LMO1 [22][23][24][25][26][27][28][29][30][31] (Table 1). These genetic models have served as valuable tools to explore and test targeted therapies and immunotherapies [32][33][34][35][36][37][38][39][40] , helping to advance the clinical trials of ALK inhibitors and CAR therapies [41][42][43][44][45] , as well as approval of DFMO by the FDA for adult and pediatric patients with highrisk neuroblastoma who have demonstrated at least a partial response to prior multiagent, multimodality therapy including anti-GD2 immunotherapy 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Unit Permissible Limits Optimum Limits In toxicological studies, especially in order to determine the toxic levels of environmental pollutants, parameters close to the natural environment of zebrafish should be provided in the laboratory environment. In this context, water quality parameters come to the fore (Table 1) [20][21][22][23]. The zebrafish is found in rivers, streams, canals, and rice fields in India, Pakistan, Bangladesh, Nepal, Myanmar, and Bhutan [22].…”
Section: Parametersmentioning
confidence: 99%
“…The zebrafish is found in rivers, streams, canals, and rice fields in India, Pakistan, Bangladesh, Nepal, Myanmar, and Bhutan [22]. Wild zebrafish distribution includes Brazil, Colombia, Malaysia, Sri Lanka, Thailand, and the United States [21,23]. Native zebrafish is found in more than 3000 institutions in more than 100 countries and is a popular aquarium fish [22,24].…”
Section: Parametersmentioning
confidence: 99%
“…In recent decades, numerous disease models have been established using zebrafish larvae to study developmental processes, such as hematology [ 194 , 195 ], and pathogenic processes in cancer [ 196 ] and infectious diseases [ 197 ]. Zebrafish models have contributed to uncovering pathogenic mechanisms and to the discovery and efficacy screening of innovative drugs [ 198 , 199 ].…”
Section: Zebrafish As a Model To Investigate Tlr2 As A Therapeutic Ta...mentioning
confidence: 99%